1996
DOI: 10.3109/07853899608999100
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spinal Epidural Haematoma: The Double Jeopardy

Abstract: Spontaneous spinal epidural haematoma is an unusual but well recognized cause of compressive myelopathy or cauda equina syndrome. Radicular pain is one of the earliest symptoms and a hallmark of spontaneous spinal epidural haematoma, as in the case of cervical spondylosis and disc prolapse. Should an epidural haematoma be located in the cervical spine, the resultant cervical radicular pain may sometimes be erroneously attributed to a cardiac cause, especially in the setting of pre-existing cardiac disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The commonest presentation of acute spinal cord haemorrhage is of neck or back pain, with a radicular component that progresses to a myelopathy over hours or days. 2 The sudden onset in this case is, in itself, highly suggestive of a vascular aetiology (ischaemic or haemorrhagic), although an acute disc protrusion can present similarly.…”
Section: Discussionmentioning
confidence: 70%
“…The commonest presentation of acute spinal cord haemorrhage is of neck or back pain, with a radicular component that progresses to a myelopathy over hours or days. 2 The sudden onset in this case is, in itself, highly suggestive of a vascular aetiology (ischaemic or haemorrhagic), although an acute disc protrusion can present similarly.…”
Section: Discussionmentioning
confidence: 70%
“…They observed only 9 (2.7%) chronic cases, defined as an evolution of more than 21 days, and most of these cases are located in the lumbar region (8/9). The differential diagnosis of SSEH includes intervertebral disc herniation, acute ischemia of the spinal cord, epidural tumor or abscess, spondylitis, transverse myelitis, or even a dissecting aortic aneurysm and acute myocardial infarction [22][23][24] . In the presented cases, we could observe two different clinical manifestations of the SSEH, probably due to their location.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included the presence of cervical or spinal lesions in the conditions that mimicked stroke;54,56 however, the lack of information regarding the disease spectrum precludes us from determining the actual frequency of SSEH among subjects with a condition mimicking stroke. Nevertheless, we believe that SSEH, especially in the cervical region, should also be included as such a clinical entity,4 thereby leading to a high index of suspicion, prompt recognition and immediate intervention, which is essential to reduce or prevent major morbidity of the disease 36. Several studies have demonstrated the safety of thrombolytic treatment in some subjects with stroke mimics,58 although there has been only a single report regarding a patient with SSEH mimicking a stroke being administered a thrombolytic agent as an initial treatment, and this was followed by urgent laminectomy without any bleeding complications 29.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, the inappropriate administration of agents used for restoring cerebral blood flow may preclude prompt surgery for SSEH, due to the patient’s modified hemostatic nature, although the information currently available may not necessarily support this concept. 29 Thus, we believe that it is necessary to take a proactive approach by adding SSEH to the list of differential diagnoses of ischemic stroke before fatal outcomes accumulate 36. Finally, it should be kept in mind that we are always facing, as do most physicians at various times, diagnostic and therapeutic dilemmas, and carefully weighing all of the options and potential outcomes on a case-by-case basis is therefore essential.…”
Section: Perspectivesmentioning
confidence: 99%